Model for Coordination of Microtubule and Actin Dynamics in Growth Cone Turning - Craig, Erin M. (Frontiers in Cellular Neuroscience, 2018)
In the developing nervous system, axons are guided to their synaptic targets by motile structures at the axon tip called growth cones, which reorganize their cytoskeleton in order to steer in response to chemotactic cues. Growth cone motility is mediated by an actin-adhesion “clutch” mechanism, in which mechanical attachment to a substrate, coupled with polarized actin growth, produces leading-edge protrusion. Several studies suggest that dynamic microtubules (MTs) in the growth cone periphery play an essential role in growth gone steering. It is not yet well understood how the MT cytoskeleton and the dynamic actin-adhesion clutch system are coordinated to promote growth cone navigation. I introduce an experimentally motivated stochastic model of the dynamic reorganization of the growth cone cytoskeleton in response to external guidance cues. Simulations of this model system demonstrate that positive feedback between MTs and the actin-adhesion clutch system gives rise to an influx of MTs to the growth cone leading edge, and local actin protrusion in response to an attractive cue. Quantitative predictions of the MT distribution and the local rate of retrograde actin flow will allow the hypothetical positive feedback mechanism to be experimentally tested.